Persian poetry in the Samanid period: a stylistic study - Mohammed, Emad Jasim; Majeid, Rana Ali (Al-Adab Journal, 2021)
In the stylistics of poetry, there are three elements of style, poetry and, consequently, language, and all three of these concepts were fluid and evolved. Therefore, the literary work, while maintaining its identity, has a relative historical value. In the stylistic study of a literary work, the aim is not to find commonalities with other literary works, but to identify what is particularly effective in it. Also, in studying a literary period with a literary current with the literature of an ethnic group, our interest is in the individual aspects and aspects of differentiation, which is the same individual style with a period and with the characteristics of ethnic literature Every literary work, at the same time, is in the general realm as well as in the particular realm. The existence of periodic styles and schools and the existence of common literary types is the best reason for the social organization of literatureThe style of poetry radiates in the language of the poet and the theme of the poet in each period is the same as the standard language of that period. This will be difficult. However, the dominant prose language of any period that is somewhat free from the linguistic influence of poetry can be accepted as a reliable criterion for measuring and recognizing the poet's linguistic deviations.